Pemberdayaan Ekonomi Masyarakat melalui Integrasi Strategi Pemasaran Online dan Offline pada Usaha Jahit - Jauharil Maknuni; Erni Wiriani; Masitah; Syamsul Rizal; Monalisa Harahap; Intan Ikhawani (PASAI : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity aims to empower the rural community’s economy through the integration of online and offline marketing in tailoring businesses. The main problems faced by the partners include limited digital literacy, low utilization of computer applications, and conventional marketing strategies. The method applied in this program was a participatory approach consisting of observation, training, mentoring, and monitoring and evaluation stages. The training focused on the use of simple computer applications, digital literacy, and integrated online–offline marketing strategies. The results indicate an improvement in partners’ ability to manage their businesses digitally, expand market reach, and enhance business independence and income. The integration of online and offline marketing has proven effective in strengthening the competitiveness of rural tailoring businesses and promoting sustainable economic empowerment. This program is expected to serve as an applicable empowerment model that can be replicated in other micro-business sectors in rural areas.